Indonesia’s Approach towards Myanmar’s Crisis: Understanding the Different Perspectives of the Democracy Process in Indonesia and Myanmar and the Role of the Military - Aswin Ariyanto Azis; Firstyarinda Valentina Indraswari; Annisa Ridhatul Khatimah; A. Qalbi Faathimah Azzahra (Jurnal Hubungan Internasional)
The recent military coup in Myanmar has shocked ASEAN countries, causing some to question ASEAN’s trajectory and approach to addressing the democratization issue. ASEAN countries have taken different approaches, as reflected in the UN General Assembly’s call to halt arms sales to Myanmar. Meanwhile, Indonesia, the world’s third-largest democracy, the largest democracy in Southeast Asia, and an ASEAN founding member, has taken the lead. Indonesia brought the issue to the ASEAN Leaders’ Meeting on 24 April 2021, resulting in a five-point consensus. However, it demonstrated no actual progress so far. Many scholars, democracy activists, and foreign policy observers consider Indonesia’s role since its success in reforming its military and turning it into a professional after having political domination. Thus, this paper examined different perspectives on how Indonesia encourages democracy in the region. Recent development depicts that Indonesia has subtly challenged the traditional non-interference policy approach. This paper enables Indonesia to maintain ASEAN’s constructive engagement. Indonesia must become a role model as the champion for a civilian rule that will not make Myanmar’s military weaker, less prosperous, or no longer be appreciated as the glue of the country—but vice versa. This paper also recommends intensifying the Indonesian military to military engagement with Myanmar.